The significance of African cooking ware in Lusitania: the case of Tróia (Portugal) - Patrícia Magalhães, Ana; Brum, Patrícia; Vaz Pinto, Inês (Rei Cretariae Romanae Fautorum Acta, 2015)
The main purpose of this paper is to document the presence of African Cooking Ware at Tróia and add this archaeological site to the diffusion map of this type of ceramics. The collection in this study has never been published and complements the ceramics studies previously made.